Kıssa-yı Ya‘Kûb Aleyhisselâm (vr. 16a-30a) adlı eser üzerinden türk dili ve edebiyatı eğitimi kapsamında din dili eğitiminin incelenmesi - Ceyhan, Solmaz (My University, 2018)
Bu çalışmada İstanbul Süleymaniye Yazma Eser Kütüphanesi Kemankeşkoleksiyonunda 541-001 numara ile kayıtlı Kıssa-yı Ya‘kûb Aleyhisselâm (vr. 16a-30a)adlı eser üzerinden din diliyle oluşturulmuş ifadelerin, kavramların, üslubun nasıl, hangiamaçla kullanıldığının tespit edilmesi, dilin bir unsuru olan din dilinin Türk dili veedebiyatı eğitimindeki yeri ve öneminin belirlenmesi amaçlanmaktadır.

In this research, through The Parable of Prophet Jacobs pbuh (peace be upon him) (vr.16a-30a) which is recorded with the number 541-001 in Kemankes Collection inSüleymaniye Writing Text Library in Istanbul, it is aimed to be determined how and forwhat objective expressions, notions, tone which are made with religion language areused and it is also aimed to be identified the place and importance of religion languagewhich is one of the elements of language in Turkish language and literature education.
Keywords: Dil; dil bilimi; Dilbilim; Din dili; Dini yönler; Education; Eğitim; Kıssa-yı Ya‘kûb; Kıssa-yı Ya‘kûb Aleyhisselâm; Koran stories; Kuran kıssaları; Language; Linguistics; Religion aspects; Religion language; The Parable of Prophet Jacobs pbuh (peace be upon him); TheParable of Prophet Jacobs; Turkish language and literature; Turkish language and literature education; Türk dili ve edebiyatı; Türkdili ve edebiyatı eğitimi